PENGARUH NON PERFORMING LOAN, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL, DAN RETURN ON EQUITY TERHADAP EARNING PER SHARE PT BANK MEGA Tbk 2014-2023 - Sonara Maulina; Rachmawaty Rachmawaty (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to determine the influence of Non Performing Loan (NPL), Operating Expenses to Operating Income (BOPO), and Return on Equity (ROE) on earnings per share at PT Bank Mega Tbk for the period 2014–2023. The research method used is quantitative, with secondary data obtained from the company’s annual financial statements. The results show that partially, NPL has no significant effect on earnings per share, as indicated by the t-value of 0.999 < t-table 2.365 and a significance level of 0.356 > 0.05. BOPO has a significant effect on earnings per share, with a t-value of 3.251 > t-table 2.365 and a significance level of 0.016 < 0.05. ROE also has a significant effect on earnings per share, shown by a t-value of 2.989 > t-table 2.365 and a significance level of 0.024 < 0.05. Simultaneously, NPL, BOPO, and ROE have a significant effect on earnings per share, indicated by an F-value of 34.643 > F-table 4.757 and a significance level of 0.001 < 0.05. The coefficient of determination of 91.8% indicates that the three independent variables are able to explain the variation in earnings per share, while the remaining 8.2% is explained by other factors not included in this research model.